Factors affecting the attractiveness of medical tourism destination: an empirical study on India- review article. - Seyama Sultana; Ahasanul Haque; Abdul Momen; Farzana Yasmin (Tehran University of Medical Sciences, 2014)
In this edge, medical tourism is not a new idea. Medical treatment is one of the essential demands of human beings and it requires high quality and intensive care. Beside western world, few developing countries are playing key roles as medical tourism destinations. India is one of the leading names among these countries. The purpose of the paper is to find the factors influencing the attractiveness of India as a health tourism destination.The study has found the major contributing factors and their relative importance in the attractiveness of the health tourism destination that is India from consumers' perspectives by conducting survey with an application of structural equation modelling approach.In Indian context, medical tourists consider service quality and cost mostly to select any medical destination. In addition they also give value to the destination competitiveness but tourist attitude is less important in comparison with other factors affecting their destination choice. Since the study has used structural equation modelling approach to test the hypothesis and figure out the relative importance of the factors, the fundamental indices such as Normed Chi square(less than 3), RMSEA (less than 0.08) and CFI (more than 0.90) values show the overall model fit of the proposed model.In order to transform a country such as India as an attractive and competitive medical tourist destination in this time of globalization, a step should be taken to control cost ensuring the quality of services.